Inflammatory disorders associated with trisomy 8‐myelodysplastic syndromes: French retrospective case‐control study. (14th November 2018) - Wesner, Nadege; Drevon, Louis; Guedon, Alexis; Fraison, Jean Baptiste; Trad, Salim; Kahn, Jean Emmanuel; Aouba, Achille; Gillard, Jerome; Ponsoye, Matthieu; Hanslik, Thomas; Gourguechon, Clement; Liozon, Eric; et al.
Abstract: Objective: We report cases of myelodysplastic syndrome/myeloproliferative neoplasms (MDS/MPN) with trisomy 8 associated with inflammatory and autoimmune diseases (IADs). Method: Data for 21 patients with trisomy 8‐MDS/MPN and IADs were analyzed and compared to 103 patients with trisomy 8‐MDS/MPN without IADs. Results: The median age of MDS/MPN patients with IADs was 67 [59‐80]. The IADs were Behçet's‐like disease in 11 (52%) patients, inflammatory arthritis in 4 (19%) and Sjögren's syndrome, autoimmune hemolytic anemia, aseptic abscess, periarteritis nodosa, Sweet's syndrome and unclassified vasculitis in one patient each. Overall, 17/21 (81%) patients with IADs received treatment (88% with steroids), with complete and partial response in 7/17 (35%) and 8/17 (47%), respectively. The effect of MDS treatment on IADs could be assessed in seven patients receiving azacytidine: five achieved remission and two partial response. As compared with the 103 trisomy 8‐MDS/MPN cases without IADs, those with IADs were more often non‐European ( P = 0.005) and had poor karyotype ( P < 0.001). We found no difference in overall survival or acute myeloid leukemia progression between trisomy 8‐associated MDS/MPN with and without IADs. Conclusion: The spectrum of IADs associated with trisomy 8‐positive MDS/MPN is dominated by Behçet's‐like disease. Steroid therapy is effective, but mostly sparing therapies are necessary. Azacytidine could be an effective alternative.